Ultrasonic-Assisted Acid Heat Treatment for the Preparation and Structural Characteristics of Pea Protein Fibers - REN Yu-kai; MOU Song-song; LI Zhi; BAI Ke-fei; LIU Xin-yi; WANG Yu-sheng; CHEN Hai-hua (Liang you shipin ke-ji)
In this study, pea protein isolate (PPI) was used as the raw material to prepare pea protein isolate fibrils (PPIF) through ultrasound-assisted acid-thermal treatment. The effects of ultrasound and acid-thermal treatment on the physicochemical properties and structural characteristics of PPIF were systematically investigated. The results revealed that after ultrasonic pretreatment, the average particle size of PPI decreased by 32 nm, and the thioflavin T fluorescence intensity increased during fibrillation, indicating that ultrasound pretreatment could reduce the activation energy required for fibril formation, thereby facilitating protein fibrillation. After ultrasonic treatment, the β-sheet content of PPIF increased from 42.67±1.76% to 44.70±0.79%, suggesting that ultrasound pretreatment enhanced hydrogen bonding and hydrophobic interactions, inducing secondary structural transitions in PPIF and promoting the formation and ordered assembly of PPIF aggregates. Acid-thermal treatment accelerated protein hydrolysis and subunit degradation, further promoting the formation of PPIF. The ultrasound-assisted acid-thermal treatment increased the solubility of PPI from 36.5% to 70.1%, while the emulsion stability index (ESI) and emulsifying activity index (EAI) increased by4.69 m2/g to 6.31 m2/g and 39.44 min to 59.33 min, respectively, significantly enhancing the solubility and emulsifying capacity of PPI. These findings suggest that ultrasound pretreatment enhances the self-assembly capability of PPIF, potentially broadening the application of PPI in novel functional foods.